PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBINA KARAKTER GENERASI Z - Yuel Sumarno; Christian Yohanes; Dalmasius Filemon; Debora Putri (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Generation Z is the nation's next generation who are technology savvy. However, it becomes a real problem if the technology used prevents them from developing and maximizing the potential they provide. This research explores more deeply the guidance and role of a teacher in developing Generation Z. The method used is qualitative with data taken based on literature study. The results obtained are that a teacher must teach with a heart full of sincerity and guidance which is carried out by entering the world of Generation Z so that the learning provided and the values can be applied to the lives of Generation Z.